Effect of a Forward and Backward Training Program on Some Inflammatory Factors and Physical Function of Older Women - Mitra Khademosharie; Azam Mollanovruzi; Marziye Azarniveh; Ayoub Saidi (University of Social Welfare & Rehabilitation Sciences, 2024)
Objectives This study aims to assess the effect of a forward and backward walking training program on some inflammatory markers and physical function of older women. Methods & Materials Twenty-four older women (aged 60-75 years) were divided into three groups of walking forward, walking backward, and control. Two groups of walking forward and walking backward, performed training three times a week for eight weeks with an exertion rate of 14-15 according to Borg's scale. Before and after the training, anthropometric factors (age, body height, body weight, and body mass index) and the muscle strength and muscle endurance were measured and blood sampling (for biochemical analysis) was conducted. Repeated measures ANOVA was used to compare the means in SPSS software, version 23, and the significance level was set at 0.05. Results The results showed that backward walking training significantly increased muscle strength and muscle endurance compared to the control and forward walking groups, but the program did not cause a significant change in the levels of tumor necrosis factor-alpha, transforming growth factor-beta, or vitamin D binding protein. Conclusion It seems that backward walking training can have a greater effect on physical function in older women compared to forward walking, and lead to a healthier life for them.